MODEL PENDIDIKAN KARAKTER PADA DAYAH DARUSSALAM LABUHAN HAJI ACEH SELATAN - Saiful Saiful (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
One of society's complaints so far was that education was focused more on hard skills and ignored soft skill (character building) education, resulting in smart students, but lacks akhlaq, morality, and mentality. Character building education aims to improve the educational process that leads to the formation of a noble character (akhlaqul karimah) of students as a whole, and balanced. The existence of Dayah in Aceh had created many graduates with high morality. The character educational model on Dayah Darussalam Labuhan Haji Aceh Selatan was: (1) The development of students regulations. (2) The development of teaching methods. (3) The development of character building education. (4) The development of students morality; and the development of students’ skills, including; practicing speech, samadiyah, prayer of the corpse, interaction etiquette, zikr, and wired.